2005
DOI: 10.2169/internalmedicine.44.41
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of the Transmission between the Colonization of Methicillin-resistant Staphylococcus aureus to Human and Environmental Contamination in Geriatric Long-term Care Wards

Abstract: Objective Transmission between human and environmental contamination from colonized methicillin-resistant Staphylococcus aureus (MRSA) remains a controversial issue. We, therefore, investigated the differences between MRSA types which colonize in humans and in the environment.Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 25 publications
(26 reference statements)
1
28
0
Order By: Relevance
“…Altogether, the frequency of MRSA positive environmental sites was 60.4%. Other studies on this topic have reported lower contamination rates in isolation rooms, such as 27.0% (19) , 24.0% (23) , 40.0% (24) , 22.0% (20) , and 54.0% (21) . However, the various studies of MRSA detection on surfaces in isolation rooms are hardly comparable, since the patient characteristics, the microbiological screening methods, the sampling regimen, as well as the manner, frequency, and effectiveness of cleaning and disinfection methods vary considerably.…”
Section: Discussionmentioning
confidence: 82%
“…Altogether, the frequency of MRSA positive environmental sites was 60.4%. Other studies on this topic have reported lower contamination rates in isolation rooms, such as 27.0% (19) , 24.0% (23) , 40.0% (24) , 22.0% (20) , and 54.0% (21) . However, the various studies of MRSA detection on surfaces in isolation rooms are hardly comparable, since the patient characteristics, the microbiological screening methods, the sampling regimen, as well as the manner, frequency, and effectiveness of cleaning and disinfection methods vary considerably.…”
Section: Discussionmentioning
confidence: 82%
“…Fifty-seven strains were from the patients’ environment. Molecular typing by PFGE with the Sma I restriction enzyme demonstrated that the predominant type of MRSA isolated from the environment changed by the minute [5]. …”
Section: Methodsmentioning
confidence: 99%
“…(Weese, J.S., 2007) discusses a number of additional possible methods for screening of the environment of animals for MRSA including the use of contact plates, swabs, electrostatic cloths, passive and active air sampling. These sampling methods were successfully used to detect MRSA in human environments (Asoh, N. et al, 2005;Shiomori, T. et al, 2001) however there is limited information on the effectiveness and sensitivity of these methods in the environment of production animals with very high loads of bacteria and dust. Other approaches included the inoculation of broth solutions with feed material or faeces and the preparation of suspensions of bedding material (Lee, J.H., 2003;Lu, J. et al, 2003).…”
Section: Sampling For Diagnosis Of Mrsa Contamination In the Environmentmentioning
confidence: 99%
“…Skin to skin contact is probably the main route of transmission between humans, humans to animals, animals to human and between animals, however contaminated materials, surfaces, food or dust can play also a role in transmitting the agent (Asoh, N. et al, 2005;Lee, J.H., 2003). This is true for both HA-MRSA and CA-MRSA.…”
Section: Vectors For Transmission Of Mrsamentioning
confidence: 99%